On Reverence and its Discontents. - White, Thomas (Cross Currents, 2019)
The article focuses on understanding of reverence as servile submission to a tyrannical transcendence, which destroys personal autonomy, is not a correct understanding of genuine reverence. It mentions impulse toward inhumanity is needed to protect, and pay homage to, the higher ideals, including compassion, that protect humanity. It also mentions affirmative aspects of religion preferring reverence, secularism, and cynicism.